PENGEMBANGAN MEDIA PEMBELAJARAN IPA MELALUI GAME INTERAKTIF BERBASIS PALIBER (PAPAN LINGKAR BERPUTAR) PADA MATERI EKOSISTEM - Tri Novita Sari; Abdul Ghoni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The development of learning media for spinning circles or paliber aimed to assist teachers in improving the delivery of Science subjects in Ecosystem material and attracted students’ interest in learning as well as made it easier for students to understand the material. Paliber media contained the materials of the ecosystem accompanied by videos and interactive game quizzes so that students were interested in it. Through interactive paliber-based games, it was hoped that the teachers would be able to use it as a learning medium that facilitated the learning process. It was interesting to understand the material provided easily. The type of research was research and development (R&D). This study indicated that the development of learning media paliber based game interactive game was feasible to use and operate only at schools. The effectiveness test using SPSS showed the value of sig (2 tailed) p= 0.000< 0.05 meaning that interactive paliber based game media effectively improved science learning outcomes on the topic of the ecosystem.